Penyuluhan Literasi Media Online Melalui Pelatihan Kewirausahaan Bagi UMKM Dalam Meningkatkan Penjualan Produk - Siregar, Nasaruddin; Dewi, Nita Komala; Nursyamsi, Sari Endah; Astuti, Hani; Ningrum, Endah Prawesti; Mujab, Saeful (Jurnal Pengabdian kepada Masyarakat UBJ, 2024)
Electronics are widely used by business people to market the products they sell and are often known as e-commerce. Apart from that, on the other hand, in assisting government programs in the creative economy sector, there are many MSMEs that have grown in several regions in Indonesia, one of which is MSMEs under Sukamekar Village, Kab. Bekasi. As many MSMEs grow, there are many obstacles experienced by MSME players, one of which is product sales strategy. The product sales strategy carried out by MSME players in Sukamekar Village, Kab. Bekasi, is still traditional, and the packaging of the goods sold does not attract buyers' interest, so the solutions provided in community service activities are: 1) providing counseling regarding online media literacy for MSMEs; 2) providing entrepreneurship training for MSMEs to increase product sales. The objectives of community service activities are: 1) increasing knowledge and understanding of social media literacy for MSMEs; 2) improving MSME sales strategies in the era of digitalization; and 3) increasing knowledge and understanding of MSME players in product packaging. The method for implementing community service activities consists of three stages, namely the preparation stage, the implementation stage (counseling and training), and the evaluation stage. Participants were representatives of MSME actors under the auspices of the Sukamekar Village office, Kab. Bekasi, as many as 20 people. The results of the activity showed that there was interest from the participants, as evidenced by the enthusiastic attitude of the participants when taking part in the activity and also proven by the results of the pre- and post-tests, which showed an increase in the participants' knowledge and skills.